Konsep Empowerment Sebagai Instrumen Pembangunan Ekonomi Islam (Telaah Kritis Pemikiran Ibnu Khaldun dan Umer Chapra) - Moh. Musfiq Arifqi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The main problem of economic development such as poverty, unemployment, asymmetry of economic among individuals could not be removed succecfully in Indonesia. One of the reasons is caused with unreadable other variables such as social law, politics, culture and so on. The size of the success Islamic economic growth is not measured only from the material achievement perspective or the results of quantity, but also from the improving religious perspective, social and society life. The motodology of this research is library research. To get more information, the reference is taken from some book that have relation with the topic. The result is that Ibn Khaldun’s thought is referring to the term